Association between human papillomavirus vaccination and serious adverse events in South Korean adolescent girls: nationwide cohort study. (29th January 2021) - Yoon, Dongwon; Lee, Ji-Ho; Lee, Hyesung; Shin, Ju-Young
Abstract: Objective: To evaluate the association between human papillomavirus (HPV) vaccination and serious adverse events in adolescent girls in South Korea. Design: Cohort study. Setting: A large linked database created by linking the Korea Immunization Registry Information System and the National Health Information Database, between January 2017 and December 2019. Participants: 441 399 girls aged 11-14 years who had been vaccinated in 2017: 382 020 had been vaccinated against HPV and 59 379 had not been vaccinated against HPV. Main outcome measures: Outcomes were 33 serious adverse events, including endocrine, gastrointestinal, cardiovascular, musculoskeletal, haematological, dermatological, and neurological diseases. A cohort design was used for the primary analysis and a self-controlled risk interval design for the secondary analysis; both analyses used a risk period of one year after HPV vaccination for each outcome. Incidence rate and adjusted rate ratios were estimated using Poisson regression in the primary analysis, comparing the HPV vaccinated group with the HPV unvaccinated group, and adjusted relative risks were estimated using conditional logistic regression in the secondary analysis. Results: Among the 33 predefined serious adverse events, no associations were found with HPV vaccination in the cohort analysis, including Hashimoto's thyroiditis (incidence rate per 100 000 person years: 52.7 v 36.3 for the vaccinated and unvaccinated groups; adjusted rate ratio 1.24, 95% confidence interval 0.78 to 1.94) and rheumatoid arthritis (incidence rate per 100 000 person years: 168.1 v 145.4 for the vaccinated and unvaccinated groups; 0.99, 0.79 to 1.25), with the exception of an increased risk observed for migraine (incidence rate per 100 000 person years: 1235.0 v 920.9 for the vaccinated and unvaccinated groups; 1.11, 1.02 to 1.22). Secondary analysis using self-controlled risk intervals confirmed no associations between HPV vaccination and serious adverse events, including migraine (adjusted relative risk 0.67, 95% confidence interval 0.58 to 0.78). Results were robust to varying follow-up periods and for vaccine subtypes. Conclusions: In this nationwide cohort study, with more than 500 000 doses of HPV vaccines, no evidence was found to support an association between HPV vaccination and serious adverse events using both cohort analysis and self-controlled risk interval analysis. Inconsistent findings for migraine should be interpreted with caution considering its pathophysiology and the population of interest.